121k views
3 votes
1/2(4-+6x)=1/3x+2/3(x+9)

User ITmeze
by
6.0k points

1 Answer

4 votes

Answer:

The value of x for the expression is 2

Explanation:

Given algebraic expression as :


(1)/(2)(4 + 6 x ) =
(1)/(3) x +
(2)/(3) ( x + 9 )

Now, solving the given expression

Or,
(1)/(2) × 4 +
(1)/(2) × 6 x =
(1)/(3) x +
(2)/(3) x +
(2)/(3) × 9

Or,
(4)/(2) +
(6)/(2) × x =
(1)/(3) x +
(2)/(3) x +
(18)/(3)

or, 2 + 3 × x =
(x)/(3) +
(2 x)/(3) + 6

or, 2 + 3 × x =
(2 x + x)/(3) + 6

or, 2 + 3 × x =
(3 x)/(3) + 6

Or, 2 + 3 × x = x + 6

or, 3 x - x = 6 - 2

Or, 2 x = 4

∴ x =
(4)/(2)

I.e x = 2

Hence The value of x for the expression is 2 Answer

User Pierre Laporte
by
6.5k points